Analisis Sistem Informasi Orang Tua Wali Mahasiswa berbasis Website Studi Kasus Universitas Muhammadiyah Magelang - Setiawan, Agus (JIU, 2016)
Abstract - Information technology was used in the world of education, needs to be done to eliminate the problem of distance, time, and place in the delivery of information. This study aims to identify and analyze the parents information system of the students based websites. The parents information system of the students is expected to provide accurate and reliable information for parents who had entrusted his son to the University of Muhammadiyah Magelang to go through the process of high-level formal education as a student. Parents are guardians of students in need of information on the progress of their children at any time in accordance with academic activities, even in relation to finance for regular payments each semester. The results of this research is a design model of parents information system of the students with integrated with KRS online system that is already running. Keywords: information systems , information systems academic , academic systems , information systems parent.